PENGARUH KOMITMEN ORGANISASI DAN MOTIVASI KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DI ALAM PURI - Diatmika, I Nyoman Crana Yuliana; Suwandana, I Gusti Made (E-Jurnal Manajemen, 2016)
This study aims to determine the influence of organizational commitment and work motivation on organizational citizenship behavior in Alam Puri Art Museum Villa Resort and Spa Penatih Denpasar. Organizational commitment and work motivation need to be considered to foster behavior organizational citizenship behavior of employees. The research was conducted on all employees at Alam Puri Art Museum Villa Resort and Spa Penatih Denpasar. Samples taken are as many as 42 employees. The sampling technique using saturation sampling (census) where the entire population sampled. The analysis technique used is multiple linear regression analysis. The results of this study indicate that organizational commitment and significant positive effect on organizational citizenship behavior and motivation positive and significant impact on organizational citizenship. The implication of this research is the manager of the company must maintain and always pay attention to how committed the organization and motivation felt by employees.
Keywords: Organizational Commitment, Work Motivation, Organizational Citizenship Behavior